(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
This article analyzes the role of sport tourism in developing volitional qualities among young people. Sport tourism is considered not only as a form of active recreation, but also as an educational and psychological environment that strengthens perseverance, self-control, responsibility, courage, discipline and purposefulness. The article explains how hiking, mountain tourism, cycling tours, orienteering, water tourism and other active forms of sport tourism influence youth character formation through physical effort, group cooperation, decision-making and overcoming natural difficulties. Scientific approaches from sport psychology, positive youth development and self-determination theory are used to justify the educational value of sport tourism. The article concludes that sport tourism can be an effective pedagogical tool for shaping strong-willed, socially responsible and resilient young citizens